1998
DOI: 10.1159/000015877
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Carotid Restenosis following Endarterectomy

Abstract: Background and Purpose: The clinical significance of restenosis after carotid endarterectomy as detected by duplex ultrasound has not been clearly established. To address this problem, we retrospectively evaluated the experience at two university-affiliated hospitals. Methods: All charts of patients with carotid endarterectomies between June 1987 and April 1995 were reviewed. Inclusion required neurological assessment and postoperative duplex ultrasound. Exclusion was based on a known source of cardioembolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This observation confirms previous studies [29, 30], while other groups found no association between ICA disease progression and recurrent ischemic events [31,32,33]. Methodological differences and different lengths of follow-up may account for these discrepancies.…”
Section: Discussionsupporting
confidence: 90%
“…This observation confirms previous studies [29, 30], while other groups found no association between ICA disease progression and recurrent ischemic events [31,32,33]. Methodological differences and different lengths of follow-up may account for these discrepancies.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of an early restenosis after CEA is approximately 13% 4 in the first 2 years. It seems that traditional risk factors of atherosclerosis are unable to predict early restenosis, 5,6 although studies are controversial. 7,8 This might reflect that the pathomechanism of an early restenosis-which is a consequence of an inflammatory response to the vessel wall leading to myointimal hyperplasia of smooth muscle cells 3 -differs from those of primary atherosclerosis.…”
mentioning
confidence: 99%
“…Reports have been published to suggest that the presence of haemodynamically significant restenosis does not affect the risk of stroke or death. Ganesan et al [18] found that cerebral ischaemia was noted in 13.3% of patients with recurrent stenosis by less than 50% compared to 19.2% of patients with more than 50% stenosis, a nonsignificant difference. Based on these data, he concluded that there is no direct association between the degree of stenosis and the number of neurological complications [19].…”
Section: Discussionmentioning
confidence: 97%